Taxonomic diversity and structure of malacofauna in stations Lavandula angustifolia L. (Lamiaceae) in the garden‘s Park of Tlemcen (Northwest Algerian) - DAMERDJI, Amina (European Journal of Applied Sciences, 2022)
The Tlemcen region is located in northwest Algeria and is characterized by a semi-arid bioclimate. An approach to the diversity of the malacofauna associated with Lavandula angustifolia was carried out in three stations in the gardens of Tlemcen Park from February to June 2015. The specific richness of Gastropods is 7 divided between two families: that of Helicidae and that of Subulinidae. The first includes two sub-families including that of Helicinae and that of Helicellinae and the second is represented by a single species. Two species are constant (Euparypha pisana and Rumina decollata), four are accessory and only one species is accidental. The relative importance of snails fluctuates between stations and between months and seasons. In February, in the first station, the specific richness is the highest equal to 6. The malacological richness is zero in June in the three stations. The largest numbers are found in the first station. Euparypha pisana (Helicidae) has a frequency of 80% and an abundance of 0.46 in the second station. The majority of malacological species are collected from the surface of the soil.